Lupus miliaris disseminatus faciei: when a rare skin disease involves the eyelid - Matsuno,Carolina Ando (2021)
ABSTRACT The authors present a case of lupus miliaris disseminatus faciei , a rare skin disease of unknown etiology, which may cause unaesthetic scarring due to its difficult treatment. The histopathological examination of epithelioid granulomas with caseating necrosis, together with the clinical features, are important for diagnosis and early treatment with better results. Despite difficult and unsatisfactory treatment, there are ongoing studies on therapy to improve aesthetic and social impairment. This case report describes an initial misdiagnosis delaying appropriate treatment, and highlights the value of physical examination and clinical judgment for another pathological examination, whenever necessary, aiming at better treatment outcomes in daily practice.